2019
DOI: 10.17509/jpjo.v4i1.10576
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Teaching Personal Social Responsibility (TPSR) Model and Cooperative Learning Model in Improving Students Tolerance and Responsibility

Abstract: This research is motivated on the basis of the decline in responsibility and tolerance of students at school, this condition is characterized by high rates of juvenile delinquency, brawls between students and moreover the influence of technology that is so strong makes students rarely socialize with the surrounding community and fellow students at school. This study reveals the differences in the TPSR model with cooperative learning models in increasing students' attitudes of responsibility and tolerance in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This shows that the application of TPSR through BBM games in fitness learning can change the character as well as the knowledge and skills of students, it happens. This is in line with or strengthens the results of research that has been done by Dupri (2019) which states that the TPSR model is better than the cooperative learning model in developing students' tolerance for physical education learning. This is confirmed by Supriyatni ( 2019 Jumareng, Aryani, & Kastrena (2021) shows that the TPSR learning model intervention has the potential to improve the attitude of responsibility or the character of students.…”
Section: Resultssupporting
confidence: 89%
“…This shows that the application of TPSR through BBM games in fitness learning can change the character as well as the knowledge and skills of students, it happens. This is in line with or strengthens the results of research that has been done by Dupri (2019) which states that the TPSR model is better than the cooperative learning model in developing students' tolerance for physical education learning. This is confirmed by Supriyatni ( 2019 Jumareng, Aryani, & Kastrena (2021) shows that the TPSR learning model intervention has the potential to improve the attitude of responsibility or the character of students.…”
Section: Resultssupporting
confidence: 89%
“…At Level 0 (irresponsible category), the results of the initial observations contained a score of 1 and the results of the study showed a score of 1, so it was concluded that there was no change in the character of the child, because the process of action was only 1 lesson, so changing a child's character is not possible in a short time [22]. from the observations it was seen that there was one child who tended to disturb his friends in playing, when this child was given a role as a train member he always refused and refused to play according to the rules.…”
Section: Discussionmentioning
confidence: 97%
“…This action is expected to stimulate students' confidence in their opinions and practice the activities that have been exemplified by the teacher. Giving praise to the work and courage of students is also needed to improve students' self-confidence [31]. Furthermore, students who have confidence will encourage mastery of their learning outcomes [32].…”
Section: Discussionmentioning
confidence: 99%